Unpacking the full potential of media facades through a fusion with Kinect technology. (1st January 2013) - Haeusler, M. Hank
Ubiquitous computing uses three basic forms for ubiquitous system devices: tabs, pads and boards. Whereas tabs and pads where early topics in post-desktop models of HCI research, the third one, boards, in particular in its extreme form as media facades, is only recently subject of discourse. The chapter works on two levels: Firstly, it offers an overview of media façade technologies and content and introduce Microsoft Kinect, a technology that enables gesture-based interactions for boards. Secondly, it lists projects and companies that have successfully used Kinect as a 'computer mouse' for interacting and introduces examples where Kinect is used for large screen interaction. The chapter contributes through providing an outlook of potential future directions through introducing the Polymedia Pixel, a technology that applies the concept of combined sensing and displaying in one device. Lastly, the chapter concludes by discussing implementation potentials of the above for ubiquitous cities.